2011
DOI: 10.1007/s11085-011-9247-5
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Impedance Study of Hot Corrosion of the Mo-Rich Ni3Al-Base Alloy IC6 at 750–800 °C Beneath Solid Na2SO4 Deposits

Abstract: A two-electrode probe was used for electrochemical impedance studies of hot corrosion kinetics of molybdenum-containing Ni 3 Al-base alloy IC6 covered with a solid Na 2 SO 4 film at 750 and 800°C in air. The alloy was subject to catastrophic corrosion at both temperatures, forming a thick porous oxide layer, as a result of the formation of Na 2 MoO 4 -MoO 3 -Na 2 SO 4 melt. The experimental temperature affected the formation of the melt, the ionic conduction of the corrosion layer, and thus the impedance chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…4 The effects of NaCl, KCl and their mixtures with sulphates have been studied in detail so far; [5][6][7][8][9][10][11] however, very few of them have been carried out using electrochemical techniques, but these techniques have been applied in some other different systems. [12][13][14][15][16][17][18][19][20][21] Thus, Aung used potentiodynamic polarisation curves, electrochemical noise and electrochemical impedance spectroscopy (EIS) in a high temperature sensor for in situ monitoring of hot corrosion. 12 The corrosion of bipolar plate and current collector materials in molten carbonate fuel cells was investigated by Zhu et al 13 using Tafel extrapolation, linear polarisation resistance, chronopotentiometry and EIS to determine corrosion rates of iron and iron based alloys in molten carbonate melts for both cathode and anode molten carbonate fuel cells environments.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 The effects of NaCl, KCl and their mixtures with sulphates have been studied in detail so far; [5][6][7][8][9][10][11] however, very few of them have been carried out using electrochemical techniques, but these techniques have been applied in some other different systems. [12][13][14][15][16][17][18][19][20][21] Thus, Aung used potentiodynamic polarisation curves, electrochemical noise and electrochemical impedance spectroscopy (EIS) in a high temperature sensor for in situ monitoring of hot corrosion. 12 The corrosion of bipolar plate and current collector materials in molten carbonate fuel cells was investigated by Zhu et al 13 using Tafel extrapolation, linear polarisation resistance, chronopotentiometry and EIS to determine corrosion rates of iron and iron based alloys in molten carbonate melts for both cathode and anode molten carbonate fuel cells environments.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Ducati et al 16 showed in one of the earliest works on this topic. Zeng et al used EIS studies for the corrosion of two-phase Cu–15Al alloy in the eutectic (Li,K) 2 CO 3 at 650°C 14 and for Ni 3 Al alloy in (Li, Na, K) 2 SO 4 at 650°C. 17 They found that the complex plane of the electrochemical impedance suggested that the fast corrosion rate of these alloys was due to the formation of a non-protective oxide and that the corrosion process was controlled by the diffusion of oxidants.…”
Section: Introductionmentioning
confidence: 99%